Indicators of the education system: Trinidad and Tobago - Singh, Narine (My University, 1995)
This paper provides information on the education system in Trinidad and Tobago and indicators of educational development in the country.
Regional Workshop on Education Indicators in the Caribbean, Georgetown, Guyana, 13-17 Mar, 1995
Keywords: Educational indicators